Factors Inhibiting the Accuracy of Outpatient Morbidity Reporting Data in SIMRS at Imelda General Hospital - Lubis, Siti Permata Sari; Simanjuntak, Esraida; Bancin, Sri Wahyuni (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
The implementation of reporting is very important for hospitals because it can be used as a comparison of visits of old patients or new patients who previously and now reporting in hospitals is divided into 2, namely Internal reporting and External reporting, reporting systems in hospitals will usually be reported monthly, quarterly, and annually. This report aims to produce relevant, accurate and timely information. To be able to produce good and correct, accurate and complete computer output data and can be accounted for is greatly influenced by the discipline of the unit towards patients. Time and place of research May 2023-August 2023 at RSU Imelda, The purpose of this study is to determine the implementation of the management of outpatient morbidity data reporting at SIMRS based on human factors (Man), Method (Method) and Facility (Machine). This type of research is descriptive qualitative. The methods used for data collection are Observation and Interview. The informants in this study amounted to 2 people consisting of 1 SIMRS officer and 1 reporting officer. The result of this study is human resources (Man) where officers still often get errors in writing early diangnosa in patient files, incompleteness of Medical Record files, lack of hospital management preparation, procedure updates and technical instructions in reporting. Facilities (Machine) where the network is often problematic makes officers late in sending reporting data, SOP (Method) where there is no specific SOP in outpatient morbidity reporting but the reporting process still runs well. The suggestion that can be given is to create a special SOP for reporting outpatient morbidity data and improve the network contained in the ruagan so that the processing in reporting can be carried out more optimally.